2020
DOI: 10.7498/aps.69.20191934
|View full text |Cite
|
Sign up to set email alerts
|

Control of spiral waves in excitable media under polarized electric fields

Abstract: Spiral waves are ubiquitous in diverse physical, chemical, and biological systems. Periodic external fields, such as polarized electric fields, especially circularly polarized electric fields which possess rotation symmetry may have significant effects on spiral wave dynamics. In this paper, control of spiral waves in excitable media under polarized electric fields is reviewed, including resonant drift, synchronization, chiral symmetry breaking, stabilization of multiarmed spiral waves, spiral waves in subexci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…An in vitro drug release study of ibuprofen adsorbed on the surface of PCL nanocomposite fibers modified with ZnO NPs showed that ibuprofen release was rapid during the first two days, but slowed in medium term (days 2–7) with the expansion of PCL. The ZnO NPs increased the adhesion of ibuprofen to PCL nanofibers, enabling a sustained release during the controllable decomposition of nanocomposite fibers over a period of 22 d. [ 177 ] Second, drugs with abundant functional groups may be blended or superposed on nanomaterials with high surface activity (e.g., LDH, nHA, GO) [ 24,181,183 ] to form composite nanocoatings with greater drug loading capacity compared to the direct deposition of drugs on the substrate surface. The deposition of a BMP‐2, PDA, and nHA composite on an AZ31 Mg alloy surface resulted in coupling of the catechol/quinone groups of PDA to BMP‐2, enabling a continuous release of BMP‐2 (35% release in 5 d and 67% in 28 d).…”
Section: Mechanisms Of Composite Nanocoatings To Improve the Utility ...mentioning
confidence: 99%
“…An in vitro drug release study of ibuprofen adsorbed on the surface of PCL nanocomposite fibers modified with ZnO NPs showed that ibuprofen release was rapid during the first two days, but slowed in medium term (days 2–7) with the expansion of PCL. The ZnO NPs increased the adhesion of ibuprofen to PCL nanofibers, enabling a sustained release during the controllable decomposition of nanocomposite fibers over a period of 22 d. [ 177 ] Second, drugs with abundant functional groups may be blended or superposed on nanomaterials with high surface activity (e.g., LDH, nHA, GO) [ 24,181,183 ] to form composite nanocoatings with greater drug loading capacity compared to the direct deposition of drugs on the substrate surface. The deposition of a BMP‐2, PDA, and nHA composite on an AZ31 Mg alloy surface resulted in coupling of the catechol/quinone groups of PDA to BMP‐2, enabling a continuous release of BMP‐2 (35% release in 5 d and 67% in 28 d).…”
Section: Mechanisms Of Composite Nanocoatings To Improve the Utility ...mentioning
confidence: 99%
“…Computer simulation is a widely used research methodology that has led to the proposal of various control methods [ 9 , 10 , 11 , 12 , 13 ]. These include light control methods [ 14 , 15 ], the polarized electric fields control method [ 9 , 16 ], the far field pacing control method [ 17 , 18 ], the control method for globally applying pulse disturbances [ 19 ], the method of applying motion controllers [ 20 ], the spiral wave de-nailing control method [ 21 ], the control method for local cooling [ 22 ], and control methods for regulating cellular ionic currents [ 23 , 24 , 25 ]. These methods have shown efficiency in controlling spiral waves and turbulent states.…”
Section: Introductionmentioning
confidence: 99%